Differences in the cellular response and signaling pathways between cisplatin and monodentate organometallic Ru(II) antitumor complexes containing a terphenyl ligand - Kisova, Anna; Zerzankova, Lenka; Habtemariam, Abraha; Sadler, Peter J; Brabec, Viktor; Kasparkova, Jana (Molecular pharmaceutics, 2011)
The new monofunctional Ru(II)-arene complex [(η⁶-arene)Ru(II)(en)Cl]+, where en = 1,2-diaminoethane and the arene is para-terphenyl (complex 1) exhibits promising cytotoxic effects in human tumor cells including those resistant to conventional cisplatin (J. Med. Chem.2008, 51, 5310). The present study is focused on the cellular pharmacology of 1 to elucidate more deeply the mechanisms underlying its antitumor effects. We have identified several cellular mechanisms induced by 1 in human ovarian carcinoma cells, including inhibition of DNA synthesis, overexpression and activation of p53, expression of proapoptotic proteins p21(WAF1) and Bax, G₀/G₁ arrest, and nuclear fragmentation as a result of apoptotic, and, to a much lower extent, also necrotic processes. Thus, 1 inhibits growth of the cancer cells through induction of apoptotic cell death and G₀/G₁ cell cycle arrest. Further investigations have shown that 1 induces apoptosis by regulating the expression of Bcl-2 family proteins. There were significant differences in cellular responses to the treatment with 1 and with conventional cisplatin, particularly in the kinetics and the extent of these responses. In addition, the distinct p53 activation profile of 1 compared with cisplatin provides an explanation for the activity of this ruthenium drug against cisplatin-resistant cells. Hence complex 1 may provide an alternative therapy in patients with acquired cisplatin resistance, particularly with respect to its very low mutagenicity and different mode of action compared to platinum antitumor drugs in clinical use.
Keywords: Ruthenium; Terphenyl Compounds; protinádorové látky; Cell Line, Tumor; western blotting; nádorový supresorový protein p53; ruthenium; Blotting, Western; lidé; Humans; Tumor Suppressor Protein p53; Cell Cycle; apoptóza; cisplatina; buněčný cyklus; nádorové buněčné linie; Cisplatin; terfenylové sloučeniny; Apoptosis; Antineoplastic Agents